Catalytic Behaviour of Mixed Metal Oxides of Ln2MO4 for the Thermal Decomposition of Carbamide - Kumari, Sima; Kumar, B.; Bishwas, B.L.; Kumar, R. (Asian Journal of Chemistry, 2010)
Mixed metal oxides of the type Ln2MO4 (Ln = Dy, Di; M = Cu, Zn, Cd) have been prepared and their catalytic behaviour for the thermal decomposition of carbamide has been studied.The mixed metal oxide samples follow the activity sequence as Dy2ZnO4 >Dy2CdO4 > Dy2CuO4. However, the oxide samples containing didymium follow the different sequences, i.e., Di2CuO4 > Di2ZnO4 > Di2CdO4. Surface area seems to be the potential factor to account for the activity The possible mechanism for the decomposition process has been suggested.